1. ## Factorisation

Can someone tell me if i have factorized correctly:

Equation is this: $x^4-6x^2+1$
First i completed the square:
$x^4-6x^2+1$
$x^4-6x^2+1-9x^2$
$(x^2-3)^2-(3x)^2$
$(x^2-3-3x)(x^2-3+3x)$
Now i use the difference of two squares where $a^2-b^2=(a-b)(a+b)$
$x^2-3x-3$
$(x-3)^2-(\sqrt3)^2$
$(x-3-\sqrt3)(x-3+\sqrt3)$
$x^2+3x-3$
$(x+3)^2-(\sqrt3)^2$
$(x+3-\sqrt3)(x+3+\sqrt3)$
$(x-3-\sqrt3)(x-3+\sqrt3)(x+3-\sqrt3)(x+3+\sqrt3)$

P.S

2. Use the \sqrt{number} command to make a square root

3. Originally Posted by Bacterius
Use the \sqrt{number} command to make a square root
oh ok

4. i got this

$x^4-6x^2+1=(x^2-3)^2-{\sqrt{8}}^2 = (x^2-3-\sqrt{8})(x^2-3+\sqrt{8})$

5. Originally Posted by Paymemoney
Can someone tell me if i have factorized correctly:

Equation is this: $x^4-6x^2+1$
First i completed the square:
$x^4-6x^2+1$
$x^4-6x^2+1-9x^2$
$(x^2-3)^2-(3x)^2$
$(x^2-3-3x)(x^2-3+3x)$
Now i use the difference of two squares where $a^2-b^2=(a-b)(a+b)$
$x^2-3x-3$
$(x-3)^2-(\sqrt3)^2$
$(x-3-\sqrt3)(x-3+\sqrt3)$
$x^2+3x-3$
$(x+3)^2-(\sqrt3)^2$
$(x+3-\sqrt3)(x+3+\sqrt3)$
$(x-3-\sqrt3)(x-3+\sqrt3)(x+3-\sqrt3)(x+3+\sqrt3)$

P.S
I'd use a dummy variable $X = x^2$ to turn it into a quadratic.

So $x^4 - 6x^2 + 1 = X^2 - 6X + 1$

$= X^2 - 6X + (-3)^2 - (-3)^2 + 1$

$= (X - 3)^2 - 8$

$= (X - 3)^2 - (\sqrt{8})^2$

$= (X - 3)^2 - (2\sqrt{2})^2$

$= (X - 3 + 2\sqrt{2})(X - 3 - 2\sqrt{2})$

Now remembering that $X = x^2$

$= (x^2 - 3 + 2\sqrt{2})(x^2 - 3 - 2\sqrt{2})$.

You could now use the difference of two squares again.

$= [x^2 - (3 - 2\sqrt{2})][x^2 - (3 + 2\sqrt{2})]$

$= \left[x^2 - \left(\sqrt{3 - 2\sqrt{2}}\right)^2\right]\left[x^2 - \left(\sqrt{3 + 2\sqrt{2}}\right)^2\right]$

$= \left(x + \sqrt{3 - 2\sqrt{2}}\right)\left(x - \sqrt{3 - 2\sqrt{2}}\right)\left(x + \sqrt{3 + 2\sqrt{2}}\right)\left(x - \sqrt{3 + 2\sqrt{2}}\right)$.

Ugly, yes, but fully factorised, yes.

6. ^
i understand the first part, however i don't understand why $3-2\sqrt2$ is square rooted?

7. Originally Posted by Paymemoney
^
i understand the first part, however i don't understand why is $= \left[x^2 - \left(\sqrt{3 - 2\sqrt{2}}\right)^2\right]\left[x^2 - \left(\sqrt{3 + 2\sqrt{2}}\right)^2\right]
$
is square rooted?
Because $3 - 2\sqrt{2} = \left(\sqrt{3 - 2\sqrt{2}}\right)^2$ and $3 + 2\sqrt{2} = \left(\sqrt{3 + 2\sqrt{2}}\right)^2$.

We had to do this to create another difference of two squares.

8. Originally Posted by Prove It
Because $3 - 2\sqrt{2} = \left(\sqrt{3 - 2\sqrt{2}}\right)^2$ and $3 + 2\sqrt{2} = \left(\sqrt{3 + 2\sqrt{2}}\right)^2$.

We had to do this to create another difference of two squares.
ok thanks